A note on Antarctic benthic mollusks collected with a beam-trawl from Breid Bay by the 25th Japanese Antarctic Research Expedition - Okutani, Takashi (1986)
P(論文) The molluscan specimens sorted out from benthos samples trawled from depths of 310 and 215m in Breid Bay were studied. A single species of Polyplacophora, 7 gastropods, one scaphopod, 6 bivalves and 2 octopod cephalopods were identified. The general compositions of the present collection represents typical shelf fauna in the Antarctic. departmental bulletin paper